EFFECTS OF MODIFIED CONSTRAINT-INDUCED MOVEMENT THERAPY FOR LOWER LIMB ON MOTOR FUNCTION IN STROKE PATIENTS: A RANDOMIZED CONTROLLED STUDY (International Journal of Physiotherapy, 2017)
Background: Few studies have examined the effectiveness of modified constraint-induced movement therapy (mCIMT) for the paretic lower limb following stroke. This study aimed to investigate the effects of mCIMT on motor function of the lower limb in stroke patients.Methods: A randomized, controlled study of 30 participants, who were randomized to 2 groups, was conducted. The study group received mCIMT, and the control group received neurodevelopmental therapy (NDT) for two weeks. All were evaluated for motor function through the Functional Ambulation Classification (FAC), Berg Balance Scale (BBS),10-Meter Walk Test, gait parameters (cadence and step length ratio) and postural symmetry ratio at pretreatment and post-treatment, like two times.Results: The improvements in BBS score, postural symmetry ratio, step length ratio, cadence and walking velocity had greater in the study group than the control group (P < 0.05). The improvement of FAC score was more pronounced in the study group (P = 0.005).Conclusion: mCIMT for paretic lower limb had superior effect against the NDT to enhance the motor function (gait parameters, balance, ambulation, and symmetry) in patients with stroke. mCIMT may be used as a new alternative treatment for lower limb rehabilitation.